A cultural analysis of the secondary housing tourism in Vilcabamba, Ecuador: The satisfaction gap between domestic and international tourists. Issue 4 (4th April 2019) - Martín, Juan Carlos; Bustamante-Sánchez, Natalia Soledad
Abstract : Purpose: This study aims to determine the level of satisfaction of secondary housing tourists in Vilcabamba. Design/methodology/approach: The analysis of satisfaction of this tourism segment in a destination is essential for the different economic agents when evaluating various policies. The analysis is based on the answers provided to 16 items in a questionnaire administered to a representative sample (281 respondents). The authors have used the fuzzy logic to reduce ambiguity in the answers associated to subjective views of human beings who express themselves linguistically. A method based on the degree of similarity to ideal solutions has been used to obtain a classification of relevant satisfaction items. Findings: The results indicate that the ideal solutions segments are represented by multicultural characteristics of second home tourists and the number of years they have been visiting Vilcabamba. The authors find that foreign tourists are more satisfied than Ecuadorians. Analyzing the most critical factors, it is seen that accessibility to the destination, socio-cultural environment and quality of water achieve a high priority. Research limitations/implications: Second home tourists' satisfaction has been studied with a limited set of 16 attributes, and some attributes also have a multidimensional nature, so a further study analyzing the scale will be needed in the future. Originality/value: The present study fills an existing gap in the literature of secondary housing tourism where the existing previous research has been mainly focused on retirees' secondary housing tourism. The study provides interesting insights into local and national authorities, as well as other economic agents, to designing strategies and planning processes of the destinations for secondary housing tourists.